Pelaksanaan Pembangunan Zona Integritas Menuju Wilayah Bebas Korupsi Dan Wilayah Birokrasi Bersih Melayani Di Kantor Imigrasi Kelas I Tpi (Tempat Pemeriksaan Imigrasi) Pekanbaru - Wihardiasty Sekar Kinasih Wihardiasty Sekar Kinasih; Sujianto Sujianto (UIR Press, 2022)
This study aims to determine: 1) The implementation of the development of an integrity zone towards a corruption-free area (WBK) and a clean bureaucratic area serving the Immigration Office Class I TPI Pekanbaru, 2) Obstacles faced by the Immigration Office Class I TPI Pekanbaru. In this study, the researcher uses the theory of Eko Prasojo (2013) which refers to 3 criteria for a good bureaucracy, namely, improving the quality of public services, being free of corruption, collusion and nepotism, and performance accountability. The findings of this study are that the Immigration Office is still in the process of developing an Integrity Zone, which is still fixing all matters related to the construction of an integrity zone at the Class I Immigration Office Pekanbaru. From other phenomena, researchers see that it is still unclear what sanctions are given if employees are involved in deviant activities. Obstacles in the implementation of the integrity zone development at the Class I Immigration Office Pekanbaru, the old work culture is still embedded so that the lack of performance in performance accountability management makes the achievement of performance not optimal.